Evaluation of Vat Collection on Imported Digital Product and Service through E-Commerce: Tax Authority Perceptions - Gilang Kusumabangsa (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Based on the tax collection principle of "The Four Maxims," this study aims to evaluate the value-added tax collection on trading through the electronic system (TTES). There has been no research evaluating the quality of TTES VAT collection in Indonesia, which can be measured using the tax collection principles outlined in "The Four Maxims." This study employs a qualitative research design with a case study approach. Data was gathered through interview techniques with three tax authorities' sources. Based on the perceptions of the sources, it is possible to conclude that TTES VAT collection in Indonesia has met the equality, convenience, and efficiency principles outlined in "The Four Maxims." However, according to the source person's perceptions, TTES VAT collection in Indonesia has not fully met the certainty principle based on "The Four Maxims."